Dung beetles (Coleoptera, Scarabaeinae) attracted to sheep dung in exotic pastures - Correa,César Murilo de Albuquerque (2013)
Dung beetles (Coleoptera, Scarabaeinae) attracted to sheep dung in exotic pastures. In this study we provide data on the abundance and richness of dung beetles (Coleoptera, Scarabaeidae, Scarabaeinae) attracted to sheep dung in exotic pastures (Brachiaria spp.). In four areas of exotic pasture pitfall traps were installed and baited with fresh sheep dung for sampling of dung beetles. A total of 2,290 individuals were captured belonging to 16 species, 10 genera and five tribes of Scarabaeinae beetles. Trichillum externepunctatum Preudhomme de Borre, 1886 and Dichotomius bos (Blanchard, 1843) were dominant. The guild of dwellers was the most abundant in pastures. We demonstrate that dung beetles are attracted to sheep dung. Since the production of both cattle and sheep in the same area is common in tropical pasturelands, results obtained here highlight the need to investigate the actual role of dung sharing (cattle dung + sheep dung) by dung beetles. It is also suggested that experiments be performed for evaluation of the ecological functions performed by dung beetles using sheep dung.